Planning targets for irrigation development - Desai, C. G. (International Food Policy Research Institute, 1990)
Although India possesses 4.9 percent of the total average annual runoff in the rivers of the world, the per capita water availability from surface as, well as groundwater sources is assessed at 3,200 cubic meters Jm3) per year, compared with the availability of more than 17,500 m3 in the Soviet Union, 6,500 m3 in Japan, and 6,200 m3 in the United States. The population that India had at the beginning of the twentieth century is likely to have increased 50 percent by the end of the century. This would further reduce the per capita availability of water. Surface water would constitute about 80 percent of this; the remainder would be from groundwater.